Transformation of Andragogic Approach in the Formation of Islamic Character of Elementary School Students: An Experimental Study Based on Local Wisdom - Anniez Rachmawati Musslifah; Faqih Purnomosidi; Mirawati Mirawati; Basir Jarah Anilon (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The purpose of the research is to analyze the effectiveness of modified andragogic models in fostering Islamic character that is integrated with local wisdom values. The method used was a quasi-experiment with a pretest-posttest control group design, involving 60 students from two Islamic boarding schools as a sample. Data were collected through participatory observation, standardized character scales, and curriculum document analysis. The results showed a significant increase in the aspects of responsibility (p=0.003) and cooperation (p=0.012) compared to the control group, with the greatest effect seen in the internalization of the value of